Serrated Leaf‐Like N‐Doped Copper Sulfide Enabling Bifunctional Oxygen Reduction/Evolution via Dual‐Mode Cathode Reactions for High Energy Density and Cycle Stability in Zinc–Air Batteries - Do Hwan Jung; Yong Hak Park; Dong Won Kim; Jong Hui Choi; Seungrae Cho; Keon‐Han Kim; Dong Gyu Park; Byungchan Han; Jeung Ku Kang (Advanced Science)
Abstract Zinc–air batteries (ZABs) are promising electrochemical energy storages, but inefficient oxygen reduction reaction (ORR) during discharging and oxygen evolution reaction (OER) during charging at their cathodes impede achieving high energy density and stable cycling. We report a serrated leaf‐like nitrogen‐doped copper sulfide (N‐CuS) cathode with conductive N 2p‐S 3p hybridized orbitals, oxygen‐transporting mesopores, and about fivefold larger surface area than Cu. A ZAB with the N‐CuS cathode exhibits a 788 mAh g−1 capacity (96% of theoretical) and a hitherto highest energy density of 916.0 Wh kg−1, surpassing one with the state‐of‐the‐art Pt/C+RuO₂ cathode (712.43 mAh g−1 and 874 Wh kg−1). Density functional theory calculations elucidate that O═O bond dissociation is 0.97 eV more favorable on N‐CuS than CuS. Subsequently, protonation of surface‐adsorbed *O to *OH occurs via dissociate (0.55 V), non‐spit associate (1.05 V), and split associate (1.05 V) pathways, with *OH then desorbing as OH‐. Under anaerobic conditions, copper oxide transitions from CuO to Cu2O (1.05 V) and eventually to Cu (0.75 V) releasing oxygen to sustain ORR. Additionally, a ZAB with the N‐CuS cathode achieves about threefold longer cyclability than one with the Pt/C+IrO₂ cathode, and about six‐fold longer cyclability than one with the Pt/C+RuO₂ cathode.